Discriminating Down Syndrome and Fragile X Syndrome based on language ability*. Issue 1 (5th December 2012) - FINESTACK, LIZBETH H.; STERLING, AUDRA M.; ABBEDUTO, LEONARD
ABSTRACT: This study compared the receptive and expressive language profiles of verbally expressive children and adolescents with Down Syndrome (DS) and those with Fragile X syndrome (FXS) and examined the extent to which these profiles reliably differentiate the diagnostic groups. A total of twenty-four verbal participants with DS (mean age: 12 years), twenty-two verbal participants with FXS (mean age: 12 years), and twenty-seven participants with typical development (TD; mean age = 4 years) completed standardized measures of receptive and expressive vocabulary and grammar, as well as a conversational language sample. Study results indicate that there are distinct DS and FXS language profiles, which are characterized by differences in grammatical ability. The diagnostic groups were not differentiated based on vocabulary performance. This study supports the existence of unique language profiles associated with DS and FXS.